2014
DOI: 10.1128/jvi.02059-13
|View full text |Cite
|
Sign up to set email alerts
|

Influenza H7N9 and H9N2 Viruses: Coexistence in Poultry Linked to Human H7N9 Infection and Genome Characteristics

Abstract: Avian influenza virus A of the novel H7N9 reassortant subtype was recently found to cause severe human respiratory infections in China. Live poultry markets were suspected locations of the human H7N9 infection sources, based on the cases' exposure histories and sequence similarities between viral isolates. To explore the role of live poultry markets in the origin of the novel H7N9 virus, we systematically examined poultry and environmental specimens from local markets and farms in Hangzhou, using realtime reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 24 publications
1
83
0
Order By: Relevance
“…Reasonable explanations for these differences from our data might be based on the different application routes (oculo-oro-nasal versus intranasal/intratracheal) and different methods of measurement of viral excretion. Further data from experimental infections of chickens, as well as genuine samples (swabs sampled from different poultry species), from the affected region rather support our findings of substantial replication in and shedding by chickens (29,31,32).…”
Section: Discussionsupporting
confidence: 69%
“…Reasonable explanations for these differences from our data might be based on the different application routes (oculo-oro-nasal versus intranasal/intratracheal) and different methods of measurement of viral excretion. Further data from experimental infections of chickens, as well as genuine samples (swabs sampled from different poultry species), from the affected region rather support our findings of substantial replication in and shedding by chickens (29,31,32).…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, our environmental surveillance data suggested that a higher ratio of H9N2 viruses had been detected in Guangdong LPM than in other regions of China (Table 1) (14). Since live poultry was the major source of H7N9 viruses (8,(15)(16)(17), the coexistence of H9N2 viruses in that susceptible population was likely to generate appropriate conditions for the emer- gence of novel reassortment variants (6). From this, we proposed that the A/Guangdong/1/2013 (H7N9) virus was most likely a product of the most recent reassortment between a novel H7N9 virus and the local H9N2 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…According to the epidemiology and sequence analyses, H7N9 virus-contaminated live-poultry markets (LPM) are regarded as the major sources of the human infections with the H7N9 virus (6)(7)(8). Therefore, after the initial report of H7N9 influenza virus infection in humans in March 2013, environmental sampling programs and enhanced sentinel hospital surveillance were implemented in Guangdong in order to identify possible cases of infection and to analyze the evolution of the virus.…”
mentioning
confidence: 99%
“…Previous studies verified the contribution of H9 virus in the process of H7N9 virus evolution [10,11]. However, to our knowledge, no study has assessed the role of H9 virus in relation to the risk of H7N9 virus contamination in the environment.…”
Section: Introductionmentioning
confidence: 85%